Children's activity and diet behaviours in the summer holidays versus school year. - Watson, Amanda; Maher, Carol; Golley, Rebecca; Dumuid, Dot; Manson, Alexandra; Tomkinson, Grant; Fraysse, Francois; Olds, Tim (Pediatric Obesity, 2023)
Summary: Background: Evidence shows children gain more weight during the summer holidays versus the school year. Objectives: To examine within‐child differences in activity and diet behaviours during the summer holidays versus the school year. Methods: Children (mean age 9.4 years; 37% male) wore accelerometers (GENEActiv; n = 133), reported activities (Multimedia Activity Recall for Children and Adolescents; n = 133) and parents reported child diet (n = 133) at five timepoints over 2 years capturing school and summer holiday values. Mixed‐effects models were used to compare school and summer holiday behaviours. Results: Children spent less time in moderate‐ to vigorous‐physical activity (−12 min/day; p = 0.001) and sleep (−12 min/day; p < 0.001) and more time sedentary (+27 min/day; p < 0.001) during summer holidays versus the school year. Screentime (+70 min/day; p < 0.001), domestic/social activities (+43 min/day; p = <0.001), self‐care (+24 min/day; p < 0.001), passive transport (+22 min/day; p = 0.001) and quiet time (+16 min/day; p = 0.012) were higher during the summer holidays, compensating for less time in school‐related activities (−164 min/day; p < 0.001). Diet quality was lower (−4 points; p < 0.001) and children consumed fewer serves of fruit (−0.4 serves; p < 0.001) during the summer holidays versus the school year. Conclusions: Children are displaying poorer activity and diet behaviours during the summer holidays, which may contribute to accelerated weight gain over the holiday period.